Intergenerational transmission of educational attainment in adoptive families in the Netherlands. (April 2017) - Scheeren, Lotte; Das, Marjolijn; Liefbroer, Aart C.
Highlights: Parental income affects educational attainment of non-adopted and adopted children. Parent's education is strongly related to education of biological children. Parent's education affects education of adopted children only limited. No robust evidence for the transmission of cultural capital. Income and genes important for intergenerational transmission of education. Abstract: To improve our understanding of the mechanisms underlying the strong association between family background and children's educational attainment, we examined intergenerational transmission within families where genetic transmission is absent. Specifically, we investigated the effect of parent's education and income on the educational attainment of their foreign-born adopted children. A large-scale register database was used, which contains information on the adoption status, educational level in secondary school and parental characteristics of all 15-year old children living in the Netherlands in the years 2011–2013. This study demonstrated that parental education mainly influenced their children's education when they were genetically related and that the influence was weak when they were adopted. Parental income, on the other hand, affected both adopted and biological children's educational attainment. Hence, the results suggested that genetic transmission and economic capital play a substantial role in intergenerational transmission of educational attainment.